Trends in public opinion about the role of social media in spreading rumors - Al- Huthaifi, Hafsa Hazza; Al- Jamal, Rabab Raafat (Arab Journal for Sciences and Research Publishing, 2019)
The study aimed at identifying trends in public opinion about the role of social media in spreading rumors, rumors and clarify the concept of types and causes of its spread, and detect cognitive effects, emotional, and behavioral on individuals as a consequence of rumors across social networking sites, and learn ways to cope with rumors. In order to achieve the objectives of the study were using descriptive survey and questionnaire is designed as a tool to collect data from a sample study, which consisted of 346 211 female and male users of social networking sites in Saudi Arabia. The study has several results, including: that the majority of users of social networking sites pertain to intensively up to 7 hours or more per day 35. 1%, the application (what’s app August) got first place in terms of its use by 76, 9, followed by the site (Twitter) by 70, 1,And reasons for use of social networking sites, primarily the ’ quick access to information, the study showed the dependency of individuals on social networking sites as a source of information, first degree approval (often) 54, 3,Social networking sites have played a great role in spreading rumors, anonymous news came out in front as the main methods of spreading rumors, and show cognitive effects access, emotional, behavioral and on individuals as a consequence of rumors, respondents emphasized the importance of addressing rumors in various ways. In the light of the results of the study, a set of recommendations and proposals to maintain the trends in public opinion and the rationalization of the role of social media in dealing with rumors, including: leveraging social media in alarm the seriousness of rumors, a culture of awareness of the need to explore information and news right before posting.